CLINICAL AND FUNCTIONAL CHANGES IN PERI-IMPLANT TISSUES DURING THEIR EARLY FUNCTIONAL LOAD IN FIXED PROSTHETICS (World Bulletin of Public Health, 2024)
This study explores the effects of early functional loading on the clinical and functional status of peri-implant tissues in patients undergoing dental implant rehabilitation. The research aimed to investigate how early masticatory loads influence microcirculation in the tissues surrounding dental implants, using laser Doppler flowmetry (LDF) to measure hemodynamic parameters. The study included 35 patients aged 20–45 years, divided into two groups: one group received delayed loading (Group 1), while the other group received early functional loading (Group 2) immediately after implant placement.